Impact of Different Land Uses on the Escherichia coli Concentrations, Physical and Chemical Water Quality Parameters in a Tropical Stream - Yee, Ling Teck; Wee, Lim Swee; Bilung, Lesley Maurice; Nyanti, Lee (Borneo Journal of Resource Science and Technology, 2016)
Rural streams are important source of water for the nearby communities. However, bacterial contamination from agriculture and human settlement may render the water unsuitable for drinking and body contact recreation. Hence, the objective of this study was to determine the impact of different land uses such as animal farming and human settlement on E. coli concentrations in the Serin River, a tropical stream. Samplings were conducted at 9 stations from September 2009 to March 2010. Results showed that E. coli concentrations ranged from 2,000-6,900,000 CFU/100 mL with E. coli concentrations in fish aquaculture water exceeding the WHO standard. Animal and crop farming stations showed the highest E. coli concentrations in the tributaries. Re-suspension from stream sediment and non-point sources such as runoff contributed to the high concentrations observed in the main river. Multiple linear regressions indicated that total suspended solids and dissolved oxygen were significant water quality parameters and they explained 68.1% of the total E. coli variations observed.